Customs - Christian Volpe Martincus; Jerónimo Carballo; Alejandro Graziano (Inter-American Development Bank (IDB), 2016)
In this paper, we estimate the effects of custom-related delays on firms' exports. In so doing, we use a unique dataset that consists of the universe of Uruguay's export transactions over the period 2002-2011 and includes precise information on the actual time it took for each of these transactions to go through customs. We account for potential endogeneity of these processing times by exploiting the conditional random allocation of shipments to different verification channels associated with the use of riskbased control procedures. Results suggest that delays have a significant negative impact on firms' exports along several dimensions. Effects are more pronounced on sales to newer buyers.
hdl:11319/7689
Keywords: F10; F13; F14; 330; Customs; Exports; Uruguay